Antibacterial Cellulose Nanocrystal-Incorporated Hydrogels With Satisfactory Vascularization for Enhancing Skin Regeneration - Lu, Haibin; Li, Xiaoling; Zhang, Mu; Xu, Changpeng; Li, Wenqiang; Wan, Lei (Frontiers in Bioengineering and Biotechnology, 2022)
Wound healing of skin defects remains a significant clinical problem due to inflammation, infection, and dysangiogenesis. The cellulose nanocrystals (CNCs) liquid crystalline phase, which facilitates cell proliferation and migration, has been shown to improve vascularization effectively. Therefore, we developed a novel injectable hydrogel based on Schiff's base and coordination of catechol-Ag. The obtained hydrogels (CCS/CCHOs-Ag) exhibited in-situ forming properties, satisfactory mechanical performance, the on-demand release of Ag, antibacterial capacity and biocompatibility. In addition, the hydrogels also could entirely cover and firmly attach wounds with irregular shapes, so as to reduce the re-injury rate. More importantly, experiments in vitro and in vivo demonstrated that CCS/CCHOs-Ag hydrogels can promote neovascularization and tissue regeneration thanks to their anti-inflammatory and antibacterial effects. In conclusion, these multifunctional hydrogels are well on the way to becoming competitive biomedical dressings, which show tremendous potential application in the field of tissue engineering.